Exploring the structure of narcissism: Toward an integrated solution. Issue 6 (22nd February 2019) - Crowe, Michael L.; Lynam, Donald R.; Campbell, W. Keith; Miller, Joshua D.
Abstract: Objective: Despite decades of work on narcissism, there remain many active areas of exploration and debate including a clear and consensual description of its underlying components. Understanding narcissism's factor structure is necessary for the precise measurement and investigation of specific psychological and behavioral processes. The aim of the current study was to explore the structure of narcissism by examining it at varying hierarchical levels. Method: Participants recruited from Amazon's Mechanical Turk ( N  = 591) completed 303 narcissism items encompassing 46 narcissism scales and subscales. Criterion variables measuring the five‐factor model, self‐esteem, aggression, and externalizing behavior were also collected. Results: A series of factor analyses reveal the factor structure of narcissism at a range of specificities. No more than five meaningful factors (i.e., Grandiosity, Neuroticism, Antagonism, Distrustful Self‐reliance, Attention‐seeking) were identified and the most parsimonious model appears to be a three‐factor structure. Narcissism scales that effectively capture each of the identified factors are identified. Factors diverged in their associations with criterion variables. Conclusions: A three‐factor model (i.e., Agentic Extraversion, Narcissistic Neuroticism, Self‐centered Antagonism) seems to be the most parsimonious conceptualization. Larger factor solutions are discussed, but future research will be necessary to determine the value of these increasingly narrow factors.